Factors associated with depression over time in head and neck cancer patients: A systematic review. Issue 6 (9th May 2019) - Korsten, Laura H.A.; Jansen, Femke; de Haan, Ben J.F.; Sent, Danielle; Cuijpers, Pim; Leemans, C. René; Verdonck‐de Leeuw, Irma M.
Abstract: Objective: To systematically review the literature on factors associated with a clinical diagnosis of depression or symptoms of depression (depression) among head and neck cancer (HNC) patients. Methods: The search was conducted in PubMed, PsycINFO, and CINAHL. Studies were included if they investigated factors associated with depression among HNC patients, they were of prospective or longitudinal nature, and English full text was available. The search, data extraction, and quality assessment were performed by two authors. Based on the data extraction and quality assessment, the level of evidence was determined. Results: In total, 35 studies were included: 21 on factors associated with depression at a single (later) time point, 10 on the course of depression, and four on both. In total, 77 sociodemographic, lifestyle, clinical, patient‐reported outcome measures, and inflammatory factors were extracted. Regarding depression at a single time point, there was strong evidence that depression at an earlier time point was significantly associated. For all other factors, evidence was inconclusive, although evidence suggests that age, marital status, education, ethnicity, hospital/region, sleep, smoking, alcohol, surgery, treatment, tumor location, and recurrence are not important associated factors. Regarding the course of depression, we found inconclusive evidence for all factors, although evidence suggests that gender, age, chemotherapy, pain, disease stage, treatment, and tumor location are not important associated factors. Conclusion: Depression at an earlier time point is significantly associated with depression later on. Several sociodemographic and clinical factors seem not to be important factors associated with depression. For other factors, further research is warranted.